2015
DOI: 10.1002/aenm.201501335
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Electronic Origins of Open‐Circuit Voltage Tuning in Organic Solar Cells Based on Ternary Blends

Abstract: loss compared to the theoretical radiative limit remains a vexing problem. [5][6][7] Within this context, organic ternary heterojunctions are becoming more widely studied as a means to optimize OPV performance. [8][9][10][11][12][13][14][15] In these blends, the use of one acceptor and multiple donors or one donor and multiple acceptors has experimentally been shown to enable improvements over a two-material blend by increasing the open-circuit voltage ( V oc ) without sacrifi cing photocurrent ( J sc ). Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 73 publications
(206 reference statements)
8
83
1
Order By: Relevance
“…As will be detailed later, the interfacial tension between two organic molecules has been demonstrated to correlate with the extent of mixing. [15,22,63,[71][72][73][74] Second, the FF of the devices increases first and then drops with increasing IEIC-Th content. There are a few clear trends in the J-V characteristics of the PTFB-O:ITIC-Th:IEIC-Th ternary devices.…”
Section: Ternary Blend Design and Photovoltaic Device Performancementioning
confidence: 98%
See 1 more Smart Citation
“…As will be detailed later, the interfacial tension between two organic molecules has been demonstrated to correlate with the extent of mixing. [15,22,63,[71][72][73][74] Second, the FF of the devices increases first and then drops with increasing IEIC-Th content. There are a few clear trends in the J-V characteristics of the PTFB-O:ITIC-Th:IEIC-Th ternary devices.…”
Section: Ternary Blend Design and Photovoltaic Device Performancementioning
confidence: 98%
“…[16,63,73,78] Such close contact could potentially lead to the formation of a mechanical alloy, which alone may not be beneficial for device performance. [73] Khlyabich et al propose that similar surface tensions between the polymer donors give rise to the organic alloy. [68] resultant devices may exhibit a tunable V OC , [72,77] which has been observed in recently published high performance ternary OSCs by Wang et al [16] There have been hypothesis about the fundamental material property that could lead to such organic alloy.…”
Section: The Role Of Surface Tension and Interfacial Tensionmentioning
confidence: 99%
“…A question arises as to why there Adv. [45,47] based on the Marcus theory (Supporting Information). 2016, 6, 1601149 www.MaterialsViews.com www.advenergymat.de (Figure 6b): we observe a systematic blueshift of the subgap CT band with the doping level, indicating that a morphology change affecting CT state energetics has occurred.…”
Section: Energetic Disorder Of the Annealed P3ht:pcbm Cellsmentioning
confidence: 99%
“…Enhancing the short circuit current density (J sc ) is possible by adding a component with a complementary absorption profile [1519]. In addition, several studies showed that also the open circuit voltage (V oc ) can be tuned by the third component [2022]. …”
Section: Introductionmentioning
confidence: 99%
“…So far, only few investigations have addressed the correlation of the underlying photophysical processes in ternary blend OSCs to phase morphology [2022]. Already in binary blend systems, a highly optimized morphology is necessary to efficiently generate and extract charge carriers.…”
Section: Introductionmentioning
confidence: 99%